Inovasi Busana Pesta Berbahan Tekstil Tradisional Bali - Ni Putu Darmara Pradnya Paramita (Institut Seni Indonesia Padangpanjang, 2022)
The community need and interest which are getting higher towards fashion world make fashion in the world develop rapidly. Fashion world development influences women one of which in party fashion. Party is one of events that usually carries certain fashion either formal or semi formal, until it is not surprising that women dress and choose clothes carefully. Many party fasion worn by community with various types of materials but they do not have their own typical yet. It can be seen from the emergence of party fashion design that is mostly offered in the market. Based on the phenomenon developing in the community and the development of textile industry especially in Bali then it is necessary to create certain innovation in creating party fasion made of Bali traditional textile namely by using Bali endek woven fabric. The methods used were observation, interview, and literature study. This creation aims to preserve and protect Bali endek cloth that is a creative cultural heritage of Bali community and this research aimed to improve the economy and prosperity of Bali community. Besides, innovation of party fashion made of Bali traditional cloth is necessary to produce fashionable clothes.